Relationship of Parenting style with adolescent social development: A case study of Form 4 students in Kolej Vokasional Kota Tinggi, Johor / Nor Hafizah Ma'at and Siti Nasihah Samshuri - Ma'at, Nor Hafizah; Samshuri, Siti Nasihah (Faculty of Administrative Science and Policy Studies, 2013)
The parenting style is very important in developing a positive adolescent social development. This research wants to know the relationship of parenting style with the adolescent social development. There are four types of parenting style which are Authoritarian Parenting Style, Authoritative Parenting Style, Permissive Parenting Style, and Uninvolved Parenting Style. Research was conduct on the Form Four Students in Kolej Vokasional Kota Tinggi Johor with the sample size of 123 students. This research was using the data correlation in order to know which parenting style have significant in contributing positive adolescent social development. Then, the result shows that the Authoritative Parenting Style has a significant in contributing positive adolescent social development.